Enhancement of the photocatalytic activity of N-doped TiO2 nanograss array films by low-temperature sulfur doping. (15th March 2020) - Hu, Te; Yan, Jiancheng; Hu, Yifei; Liu, Tongyang; Guan, Sujun; Lu, Yun; Hao, Liang; Fan, Touwen; Chen, Dongchu
Abstract: Moderate in-situ chemical oxidation of Ti meshes was used to prepare nitrogen-doped (N-doped) anatase TiO2 nano-grass array films with urea as the nitrogen source. Further sulfur doping through immersion of the films in a thiourea solution at a relatively low temperature of 353 K was subsequently performed to enhance the visible-light-driven photocatalytic activity of the films. SEM images confirmed that the loose microstructure of the nanograss arrays became compact after N-doping or N, S co-doping. N-doping and N, S co-doping decreased the band gap values of the TiO2 films and increased the effective visible light utilization. XPS analysis revealed that nitrogen mainly existed in interstitial form. Subsequent sulfur ions appeared as S 6+, S 4+, and S 2−, with S 6+ and S 4+ replacing Ti 4+, and S 2− replacing O 2−, respectively. With an increase in the urea treatment time, the sulfur ions were oxidized, achieving higher valence states. S 6+ substitution resulted in a charge imbalance, which could only be neutralized by hydroxide ions. The imbalance made it easier for water that had settled on the TiO2 films to chemically dissociate, and thereby generating hydroxyl radicals. OH radicals as well as Ο 2 − radicals played a significant role in the degradation of RhB dye. The RhB decolorization activity achieved by the N, S co-doped samples was 48 times that of the undoped samples.